Why Are Connection Charges So High? : An Analysis of the Electricity Sector in Sub-Saharan Africa - Blimpo, Moussa (World Bank, Washington, DC, 2018)
This study develops and structurally estimates a model of household and electric utility behavior to describe how the low access rates and high connection charges that are common in the Sub-Saharan Africa region arise from regulated electricity tariffs being set too low. As a result, the utilities lose money on each connected customer and low electricity consumption by households makes it difficult to recover the cost of providing a connection. For each possible choice of the regulated tariff, the optimal upfront connection charge is computed that will maximize profits for the utility in its service territory. Higher tariffs are associated with lower optimal connection charges and higher electrification rates. Nonetheless, due to households' low willingness to pay for electricity services, the equilibrium electrification rates in the model are much lower than 100 percent. Future advances in electrification will require higher incomes, increased coverage of the distribution network, and lower connection costs.